Pengaruh Kemandirian dan Kreativitas Belajar terhadap Prestasi Belajar Matematika dalam Pembelajaran Daring - Sari, Pratidina Puspita; Hidayah, Nurina; Najibufahmi, Muhammad (Circle: Jurnal Pendidikan Matematika, 2021)
This research is motivated by the corona virus (Covid-19) outbreak which has an impact on the learning system in schools. Learning that is generally done face-to-face has been converted into online learning. This has an impact on the low learning achievement, because the character of students is still dependent on the teacher in receiving the material completely. Therefore, a research was conducted which aims to determine the effect of self-regulated learning and creativity learning on mathematics learnng achievement in online learning of seventh grade students SMP Muhammadiyah Pekajangan. The data were obtained through a questionnaire on self-regulated leaning and a questionnaire on creativity learning and a learning achievement test. The data analysis technique consisted of prerequisite analysis, simple regression analysis and multiple regression. The results show that (1) there was a significant effect of self-regulated learning on learning achievement with the effect was 33.3%, (2) there was a significant effect of creativity learning on learning achievement with the effect was 14.0%, and (3) there was a significant effect of self-regulated leaning and creativity learning collectively on learning achievement with the effect was 33.4%.